A nadA Mutation Confers Nicotinic Acid Auxotrophy in Pro-carcinogenic Intestinal Escherichia coli NC101 - Lopez, Lacey R.; Barlogio, Cassandra J.; Broberg, Christopher A.; Wang, Jeremy; Arthur, Janelle C. (Frontiers in Microbiology, 2021)
Inflammatory bowel diseases and inflammation-associated colorectal cancer are linked to blooms of adherent-invasive Escherichia coli (AIEC) in the intestinal microbiota. AIEC are functionally defined by their ability to adhere/invade epithelial cells and survive/replicate within macrophages. Changes in micronutrient availability can alter AIEC physiology and interactions with host cells. Thus, culturing AIEC for mechanistic investigations often involves precise nutrient formulation. We observed that the pro-inflammatory and pro-carcinogenic AIEC strain NC101 failed to grow in minimal media (MM). We hypothesized that NC101 was unable to synthesize a vital micronutrient normally found in the host gut. Through nutrient supplementation studies, we identified that NC101 is a nicotinic acid (NA) auxotroph. NA auxotrophy was not observed in the other non-toxigenic E. coli or AIEC strains we tested. Sequencing revealed NC101 has a missense mutation in nadA, a gene encoding quinolinate synthase A that is important for de novo NAD biosynthesis. Correcting the identified nadA point mutation restored NC101 prototrophy without impacting AIEC function, including motility and AIEC-defining survival in macrophages. Our findings, along with the generation of a prototrophic NC101 strain, will greatly enhance the ability to perform in vitro functional studies that are needed for mechanistic investigations on the role of intestinal E. coli in digestive disease.